A Multicomponent Thermal Fluid Numerical Simulation Method considering Formation Damage - Xinan Yu; Xiaoping Li; Shuoliang Wang; Yi Luo (Geofluids)
Multicomponent thermal fluid huff and puff is an innovative heavy oil development technology for heavy oil reservoirs, which has been widely used in offshore oilfields in China and has proved to be a promising method for enhancing oil recovery. Components of multicomponent thermal fluids contain many components, including carbon dioxide, nitrogen, and steam. Under high temperature and high pressure conditions, the complex physical and chemical reactions between multicomponent thermal fluids and reservoir rocks occur, which damage the pore structure and permeability of core. In this paper, the authors set up a reservoir damage experimental device, tested the formation permeability before and after the injection of multiple-component thermal fluids, and obtained the formation damage model. The multicomponent thermal fluid formation damage model is embedded in the component control equation, the finite difference method is used to discretize the control equation, and a new multielement thermal fluid numerical simulator is established. The physical simulation experiment of multicomponent thermal fluid huff and puff is carried out by using the actual sand-packed model. By comparing the experimental results with the numerical simulation results, it is proved that the new numerical simulation model considering formation damage proposed in this paper is accurate and reliable.